Comparison of the Toxicity of Wofasteril Peracetic Acid Formulations E400, E250, and Lspez to Daphnia magna, with Emphasis on the Effect of Hydrogen Peroxide. (20th February 2015) - Liu, Dibo; Straus, David L.; Pedersen, Lars‐Flemming; Meinelt, Thomas
Abstract: Commercial peracetic acid (PAA) formulations are acidic mixtures of PAA, hydrogen peroxide (H2 O2 ), acetic acid, H2 O, and stabilizers to maintain the equilibrium of the concentrations. Different PAA formulations show diverse PAA : H2 O2 ratios, potentially leading to different toxicities at the same PAA concentration due to the different concentrations of H2 O2 and stabilizers used. To confirm any potential differences in toxicity, we performed 24‐h toxicity tests using Daphnia magna with three commercial PAA formulations (Wofasteril): E400, E250, and Lspez. The experiments were carried out in standard dilution water and with increased water hardness, salinity, or dissolved organic carbon to reflect various natural conditions. Results showed that the toxicity to Daphnia was greatest for Lspez, intermediate for E250, and lowest for E400. An E400 + H2 O2 mixture, which possessed a composition theoretically identical to the E250 formulation, had toxic effects and 24‐h LC50 values similar to those of E250. This indicates an additive effect of H2 O2 on the toxicity of PAA formulations. Moreover, a significant positive correlation was found between Daphnia mortality and the 3‐h concentration of total peroxide (PAA and H2 O2 ), with an r ‐value higher than that of PAA alone. A significant negative correlation between the total peroxide : PAA molar ratio and the 24‐h LC50 value was observed, indicating that the toxicity of PAA formulations to Daphnia is due to the combined effect of both PAA and H2 O2 .